2022
DOI: 10.3390/cells11152341
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Heat and Osmotic Stress on Suberization of Arabidopsis Roots

Abstract: The simultaneous occurrence of heat stress and drought is becoming more regular as a consequence of climate change, causing extensive agricultural losses. The application of either heat or osmotic stress increase cell-wall suberization in different tissues, which may play a role in improving plant resilience. In this work, we studied how the suberization process is affected by the combination of drought and heat stress by following the expression of suberin biosynthesis genes, cell-wall suberization and the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Data from the eFP browser database ( ) showed that the expression of MYB107 , MYB9 , FAR4 , FAR5 , CYP86B1 , GPAT5 , ASFT , LTPG15 , ABCG6 , ABCG20 , and ABCG23 was induced in Arabidopsis seedlings after 3 h of 10 µM ABA treatment ( Figure S4 ). Exogenous ABA treatment was also found to induce expression of the fluorescent protein-encoding gene mCITRINE-SYP122 in Arabidopsis roots under the control of the GPAT5 promoter ( Barberon et al., 2016 ; Shukla et al., 2021 ; Leal et al., 2022 ). In kiwifruit, the expression of AchnMYB107 , which is a homologue of AtMYB107 , is increased in response to exogenous ABA treatment, followed by the induction of AchnCYP86A1 and AchnFAR expression, which are speculated to encode a fatty acid ω-hydroxylase and fatty acyl reductase, respectively, responsible for wound suberization in kiwifruit ( Wei et al., 2020a ; Wei et al., 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the eFP browser database ( ) showed that the expression of MYB107 , MYB9 , FAR4 , FAR5 , CYP86B1 , GPAT5 , ASFT , LTPG15 , ABCG6 , ABCG20 , and ABCG23 was induced in Arabidopsis seedlings after 3 h of 10 µM ABA treatment ( Figure S4 ). Exogenous ABA treatment was also found to induce expression of the fluorescent protein-encoding gene mCITRINE-SYP122 in Arabidopsis roots under the control of the GPAT5 promoter ( Barberon et al., 2016 ; Shukla et al., 2021 ; Leal et al., 2022 ). In kiwifruit, the expression of AchnMYB107 , which is a homologue of AtMYB107 , is increased in response to exogenous ABA treatment, followed by the induction of AchnCYP86A1 and AchnFAR expression, which are speculated to encode a fatty acid ω-hydroxylase and fatty acyl reductase, respectively, responsible for wound suberization in kiwifruit ( Wei et al., 2020a ; Wei et al., 2020b ).…”
Section: Discussionmentioning
confidence: 99%